Plasma Levels of Keratinocyte Growth Factor Are Significantly Elevated for 5 Weeks After Minimally Invasive Colorectal Resection Which May Promote Cancer Recurrence and Metastasis - Shantha Kumara, H. M. C.; Shah, Abhinit; Miyagaki, Hiromichi; Yan, Xiaohong; Cekic, Vesna; Hedjar, Yanni; Whelan, Richard L. (Frontiers in Surgery, 2021)
Background: Human Keratinocyte Growth Factor (KGF) is an FGF family protein produced by mesenchymal cells. KGF promotes epithelial cell proliferation, plays a role in wound healing and may also support tumor growth. It is expressed by some colorectal cancers (CRC). Surgery’s impact on KGF levels is unknown. This study’s purpose was to assess plasma KGF levels before and after minimally invasive colorectal resection (MICR) for CRC. Aim: To determine plasma Human Keratinocyte Growth Factor levels before and after minimally invasive colorectal resection surgery for cancer pathology. Method: CRC MICR patients (pts) in an IRB approved data/plasma bank were studied. Preoperative (preop) and postoperative (postop) plasma samples were taken/stored. Late samples were bundled into 7 day blocks and considered as single time points. KGF levels (pg/ml) were measured via ELISA (mean± SD). The Wilcoxon paired t-test was used for statistical analysis. Results: 80 MICR CRC patients (colon 61%; rectal 39%; mean age 65.8± 13.3) were studied. The mean incision length was 8.37 ± 3.9 and mean LOS 6.5±2.6 days. The cancer stage breakdown was; I, 29%, II, 34%, III, 32% and IV, 5%. The mean preop KGF level was 17.7± 8.3 pg/ml; significantly elevated (p<0.05) mean levels (pg/ml) were noted on postop day (POD) 1 (24.7± 12.8; n=80), POD 3 (27.3±18.3, n=76), POD7-13 (23.4±12.6, n=50), POD14-20(23.6±12.1, n=33). ), POD 21-27 (19.2 ±6.6, n=15) and on POD 28–34 (20.1 ±8.7, n=12). Conclusion: Plasma KGF levels were significantly elevated for 5 weeks after MICR for CRC. These changes, together with similar persistent elevations of 12 other proangiogenic proteins may stimulate angiogenesis in residual tumor deposits after surgery. Further study is needed.